Evaluation of Attitude of the Endodontists and General Practitioners towards the Importance of Reciprocating motion in Endodontic treatment (Journal of Hama University, 2024)
The reciprocating  motion is defined from a pulpal point of view as a succession of unequal and repetitive backward and forward movements, and the current developments in files that work with reciprocating  motion showed a qualitative leap in the techniques of preparing the root canals and the ability of these files to prepare well for the root canals in terms of preserving the canal anatomy and reducing From the protection of the breakage of the radiators.The aim of this research Was to investigate the opinion of general dentists and endodontists regarding the importance of reciprocating  motion during dental treatment. The sample consists of 170 Endodontists and general dentists in Syria, and the questionnaire consisted of 8 questions about the importance of the reciprocating motion and the percentages of dependence on it in preparing the root canals. The percentage of dentists who prefer reciprocating  motion (37.03%) was greater than that of general dentists (23.07%). The percentage of using manual files on the alternating fist was low (18.3%), while 91.13% of the participants believe that the time taken to prepare the root canal using the reciprocating  motion is longer than when using the rotational motion, but the reciprocating  motion is characterized by the ability to maintain the centrality The canal (91.13%) also reduces the fracture of endodontic instruments (85.44%) The data were analyzed after data collection using chi-square analysis with a significance level of 0.05.
Keywords: Root canal Preparation , reciprocating movement ,Hand Files, Instruments Fracture